Regulation of tissue factor in NT2 germ cell tumor cells by cisplatin chemotherapy. Issue 3 (September 2015) - Jacobsen, Christine; Oechsle, Karin; Hauschild, Jessica; Steinemann, Gustav; Spath, Brigitte; Bokemeyer, Carsten; Ruf, Wolfram; Honecker, Friedemann; Langer, Florian
Abstract Background Patients with germ cell tumors (GCTs) receiving cisplatin-based chemotherapy are at increased risk of thrombosis, but the underlying cellular and molecular mechanisms remain obscure. Objective To study baseline tissue factor (TF) expression by GCT cell lines and its modulation by cisplatin treatment. Methods TF expression was assessed by single-stage clotting and thrombin generation assay, flow cytometry, ELISA, and Western blot analysis. Cell cycle analysis and detection of phosphatidylserine (PS) membrane exposure were carried out by flow cytometry. TF mRNA was analyzed by quantitative RT-PCR. Results Significant expression of TF-specific procoagulant activity (PCA) was detected on three non-seminoma (NT2, 2102Ep, NCCIT) and one seminoma cell line (TCam-2). Treatment with 0.4 μM cisplatin (corresponding to the IC50) for 48 hrs increased TF PCA on NT2 cells 3-fold, an effect that was largely independent of PS exposure and that could not be explained by translocation of active TF from intracellular storage pools. Cisplatin-induced TF PCA expression in NT2 cells did not occur before 12 hrs, but was steady thereafter and accompanied by a 2-fold increase in total and surface-located TF antigen. Importantly, increased TF gene transcription or production and release of an intermediate factor were not involved in this process. Cell cycle analysis suggested that cisplatin-induced G2/M arrest resulted in an accumulation of procoagulant TF on the membrane surface of NT2 cells. Conclusions In addition to induction of apoptosis/necrosis with PS-mediated activation of preformed TF, cisplatin may alter the procoagulant phenotype of GCT cells through an increase in total cellular TF antigen.